(untitled) (Community Based Medical Journal, 2013)
This retrospective study was done in the Department of Dentistry, CBMCB hospital from January2009 to December2010. 223 patients who underwent RCT were purposively selected. Male-female ratio was 1:1.4, mean age of patients were 28.4 years. Most common indication of RCT was gross caries 69.95%, common complications were fractured crown 11(57.89%), tenderness 5(26.32%), discharging sinus 2(10.53%). Over all success rate of RCT was 91.48%. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14178 Community Based Medical Journal Vol.2(1) 2013 29-33